How do States Inform Nurses of Their Policies for Mandatory Reporting of Child Maltreatment?. (May 2022) - Mudrick, Nancy R.; Blackwell, Julia; Watts, Cherisse; Smith, Carrie Jefferson; Williams, Alex; Nielsen, Kyrian A; Clark, Lauren
Every state includes nurses as mandated reporters of suspected child maltreatment, and each state has its own law and policy regarding what is reportable and reporting requirements. These differences mean that generic training on child abuse and reporting needs to be augmented by practical state-specific information. In nearly every study of nurses, participants report having inadequate child abuse training. This paper presents an analysis of the information states post on their websites to educate nurses to appropriately identify and report suspected child abuse or neglect. Specifically, this study aims to answer the following questions: (1) how do mandated reporting laws that apply to nurses vary by state, (2) what information do states provide on their child protection and Board of Nursing websites about child maltreatment and mandatory reporting, and (3) what training resources do states make available on their websites to educate nurse mandatory reporters to ably fulfill their obligation? Data on state-by-state practices regarding mandated reporting of child abuse were gathered from the Rape, Abuse, & Incest National Network (RAINN) database, review of state statutes, Child Welfare Information Gateway, Board of Nursing sites, and the Nursing Licensure Compact (NLC) website. This analysis found that states provide little guidance or education about their child maltreatment laws, and few have resources targeted for nurses. Given rising membership in the NLC it is critical for nurses to have education about state specific mandated reporting requirements. States should consider adding mandatory reporting training as a requirement for licensure and for continuing education.